Examining Depression among Breast Cancer Patients in Nigeria: A Scoping Review : Depression among BC patients - Eseadi, Chiedu; Amedu, Amos Nnaemeka (Archives of Breast Cancer, 2024)
Background: Depression is one of the major mental health problems that hinder recovery of breast cancer patients. Comorbidity of depressive disorder and breast cancer is a complicated medical condition globally. This study examined depression among breast cancer survivors in Nigeria. Methods: This study used a scoping review approach to explore four databases, which include Google Scholar, PubMed, Medline and Scopus. The search produced 50 records using formulated search terms formulated which are relevant to the topics. Of the 50 records selected, 42 articles that did not meet eligible requirements were removed, and 8 records were included. Results: this study revealed that depression is one of the psychological problems that patients with breast cancer experience in Nigeria. In addition, this review revealed that psychological interventions such as cognitive behavioural therapy (CBT) and pilot cognitive restructuring are effective in reducing the depressive symptoms among breast cancer patients in Nigeria. Conclusion: Based on the published peer reviewed articles, depression is major mental health problem among breast cancer patients in Nigeria, and CBT and psychoeducation have been found to be effective treating depression symptoms in Nigeria. However, more studies are needed in the northern parts of the country since most of the review studies were done in the southern parts of the country.